Fetal Cartilage Progenitor Cells in the Repair of Osteochondral Defects - Bruno C. Menarim, DVM, PhD; Chan Hee Mok, PhD; Kirsten E. Scoggin, PhD; Alexis Gornik, DVM; Emma N. Adam, DVM, PhD; Shavahn C. Loux, PhD; James N. MacLeod, VMD, PhD (JBJS Open Access)
Background:. Therapies for cartilage restoration are of great interest, but current options provide limited results. In salamanders, interzone (IZN) tissue can regenerate large joint lesions. The mammalian homolog to this tissue exists during fetal development and exhibits remarkable chondrogenesis in vitro. This study analyzed the potential of equine IZN and adjacent anlagen (ANL) cells to regenerate osteochondral defects. Methods:. Osteochondral defects were created in the knee of immunosuppressed rats and were grafted with cell pellets from either equine fetal IZN, equine fetal ANL, adult fibroblasts, or adult chondrocytes, or they were left untreated. Osteochondral repair was assessed after 2, 6, and 16 weeks. Results:. Untreated lesions unexpectedly failed to represent critical-sized defects and at 2 weeks exhibited new subchondral bone covered by a fibrocartilage layer that thinned over time. Fibroblast-treated defects filled with soft fibrous tissue. Chondrocyte-treated repair tissue exhibited strong proteoglycan and COL2 staining but poor integration to the adjacent bone. Defects treated with IZN, ANL, or chondrocyte pellets developed hyaline cartilage with increasing safranin-O and collagen II staining over time. IZN and ANL repair tissues exhibited some evidence of zonal architecture such as native cartilage and the best bone integration; nonetheless, they developed exuberant growth, often causing patellar instability and osteoarthritis. Conclusions:. IZN or ANL cells exhibited some potential to recapitulate developmental features during cartilage repair. However, identifying regulatory determinants of IZN and ANL-derived overgrowths is necessary. Clinical Relevance:. Studies grafting IZN or ANL tissues in larger animal models with regular immune functions may provide additional insights into improving osteochondral regeneration.